Faktor-faktor yang mempengaruhi kinerja sistem informasi akuntansi padaperbankan di kota Pekanbaru - Ananda, Riski Marisa; L, Al-azhar; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine the effect of participation personnel information system, capability of personnel information system, training and education of personnel information system, organization size, and top management support for performance of accounting information system.The population in this study is the banking companies in the city of Pekanbaru period 2014. The stastical method used to test the research hypothesis is a multiple regression using SPSS 17 software. Based on the results of t test with significance level α of 5%, it can be concluded that the size of the organization does not affect the performance of accounting information systems, While the participation of personnel information system, the capability of personnel information system, training and education of personnel information system, top management support effect on the performance of accounting information systems.Based on the results of testing the coefficient of determination is known that the value of Adjusted R Square 0.632, or approximately 63.2%. This means that the magnitude of the independent variables that proxy participation personnel information system, capability of personnel information system, training and education of personnel information system, organization size, and top management support can explain the dependent variable is the performance of accounting information systems at 63.2%, while the balance of 36.8% is explained by other variables not included in the study.Keywords:Participation of personnel information system, capability of personnel information system, training and education of personnel information system, organization size, top management support, performance of accounting information system.